Governance for Takaful Operators (Islamic Insurance Companies) - Amirul Afif Muhamat (Türkiye İslam İktisadı Dergisi)
The article reviews past literature on the governance aspect of takaful operators. This aspect has been given limited attention in literature on Islamic finance compared to other components such as Islamic banking and Islamic capital market. Therefore, major articles concerning governance issues of takaful operators are discussed and special consideration has been given to the UK Stewardship Code and the Malaysian Rating Corporation (MARC) guidelines for Islamic financial institutions. Interestingly, this article suggests that the Malaysian Rating Corporation (MARC) guidelines for Islamic financial institutions and the UK Stewardship Code should be used as references in order to develop dedicated stewardship guideline for Islamic financial institutions like takaful operators. The stewardship theory is compatible with the Islamic notion of al-falah. Therefore, by having specific stewardship guidelines for the takaful operators it can further encourage policyholders’ engagement with the takaful operators’ management. Last but not least, this article contributes to discussion in this area especially on the possibility of having a set of stewardship guidelines for the Islamic financial institutions (IFIs) such as takaful operators.